Deeply embedded protostelar population in the 20 km s-1 cloud of the centralmolecular zone - Lu, Xing; Zhang, Qizhou; Kauffmann, Jens; Pillai, Thushara; Longmore, Steven N.; Kruijssen, Diederik; Battersby, Cara; Gu, Qiusheng (The astrophysical journal. Part 2, Letters, 2015)
We report the discovery of a population of deeply embedded protostellar candidates in the 20 km s−1 cloud, one of the massive molecular clouds in the Central Molecular Zone (CMZ) of the Milky Way, using interferometric submillimeter continuum and H2O maser observations. The submillimeter continuum emission shows five 1 pc scale clumps, each of which further fragments into several 0.1 pc scale cores. We identify 17 dense cores, among which 12 are gravitationally bound. Among the 18 H2O masers detected, 13 coincide with the cores and probably trace outflows emanating from the protostars. There are also 5 gravitationally bound dense cores without H2O maser detection. In total, the 13 masers and 5 cores may represent 18 protostars with spectral types later than B1 or potentially growing more massive stars at earlier evolutionary stages, given the non-detection in the centimeter radio continuum. In combination with previous studies of CH3OH masers, we conclude that the star formation in this cloud is at an early evolutionary phase, before the presence of any significant ionizing or heating sources. Our findings indicate that star formation in this cloud may be triggered by a tidal compression as it approaches pericenter, similar to the case of G0.253+0.016 but with a higher star formation rate, and demonstrate that high angular resolution, high-sensitivity maser, and submillimeter observations are promising techniques to unveil deeply embedded star formation in the CMZ.
Gesehen am 03.06.2020
Im Titel ist "-1" in s-1 hochgestellt